Implementasi Pemenuhan Nafkah pada Keluarga Generasi Sandwich di Yayasan Diniyah Pekanbaru Perspektif Sosiologi Keluarga - Ayu SuryaNensy; Sofia Hardani; Arisman Arisman (Khulasah : Islamic Studies Journal, 2025)
The term "sandwich generation" has recently been used to describe a situation where individuals, particularly young adults, face the dual burden of caring for elderly parents while also supporting children who still depend on them. The portrayal of the sandwich generation as being trapped and burdened with complaints does not entirely align with the Islamic values regarding the role of men. A study conducted at Yayasan Diniyah Pekanbaru identified nine teachers and staff as members of the sandwich generation. However, it was found that most of them were able to adequately meet their family’s financial needs, contrasting with other studies in Indonesia that often highlight significant challenges. This research aims to examine how the sandwich generation at Yayasan Diniyah Pekanbaru fulfills their family’s financial responsibilities, identify supporting factors, and analyze these practices from the perspective of family sociology. Using field research methods with a qualitative approach, the study revealed that sandwich-generation families at Yayasan Diniyah Pekanbaru successfully manage their economic responsibilities. Most respondents demonstrated stable income sources and effective financial management systems. While there were variations in spousal roles, financial management, and the involvement of extended family members, each family operated based on its own principles and objectives. Key supporting factors included religious education, financial management skills, and family values. From a family sociology perspective, an analysis using the functional theory indicates that sandwich-generation families who can meet their responsibilities without feeling burdened are those who successfully perform their economic, social, and emotional functions optimally. This study concludes that not all members of the sandwich generation struggle or feel burdened when fulfilling their family’s needs, including those of their children, spouses, parents, or other dependents.